MALARIA SEREBRAL - Kiking Ritarwan* (NEURONA, 2010)
INTRODUCTION CEREBRAL MALARIA IS THE MOST SEVERE NEUROLOGICAL COMPLICATION OF PLASMODIUM FALCIFARUM IT OCCURS IN ABOUT 12 IN PATIENTS INFECTED WITH PLASMODIUM FALCIFARUM AND THE MORTALITY IS STILL HIGH